Pengaruh Komitmen Organisasi Dan Kemampuan Serta Motivasi Terhadap Kepuasan Kerja Dan Kinerja Pegawai Badan Pendidikan Dan Pelatihan Kota Tarakan - Anwar Anwar (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study was to determine the effect Organizational Commitmen and Ability and the Motivation on Satisfaction and Performance Of Education and Training Agency’s employees and aims to 1) identify and analyze the direct effect of organizational commitmen, ability and motivation of the Education and Training Agency’s employees of Tarakan City ; 2) identify and analyze the direct effect of organizational commitmen, ability, motivation and job satisfaction with the performance of the Education and Training Agency’s employees of Tarakan City ; 3) identify and analyze the indirect influence of organizational commitmen, ability and motivation of the performance through job satisfaction of the Education and Training Agency’s employees of Tarakan City ;The method used descriptive and explanatory survey to employees who work in Education and Training Agency of Tarakan City. The draft questionnaire has been prepared in advance, then distributed to a sample of the population of physicians in the Education and Training Agency of Tarakan City number 46. This study uses analysis tools such as path analysis is done through the help of IBM software SPSS 21 and previously was based on the results of recapitulation of the answers of all respondents.The results showed that there is a direct effect organizational commitmen, ability and motivation to job satisfaction. There is a direct effect of organizational commitmen, ability, motivation and job satisfaction with the performance. There is the indirect effect of organizational commitmen, ability and motivation on the performance through job satisfaction of the Education and Training Agency’s employees of Tarakan City.